The Transition to Renewable Energy Economies and Its Role in Achieving Sustainable Development in Algeria - Abdelkader NOUREDDINE (Dirassat Journal Economic Issue, 2025)
The aim of this research was to investigate how Algeria's shift to renewable energy economies and attaining sustainable development in all three of its dimensions affect the country's economy, society, and environment. The analytical approach was adopted in this study. The results showed that renewable energy occupies an important position in Algeria through investment in renewable energy and enacting laws and decrees that support and finance institutions active in this field locally and internationally with the aim of transitioning to green and sustainable energy. This embodies governmental initiatives and policies to lessen reliance on fossil fuels and shows a clear political vision in the field of renewable energy. Additionally, the research revealed that in renewable energy help Algeria achieve the seventh aim of the Sustainable Development Goals in three areas: environmental protection against pollution, social development, and economic development.